Evaluation of the policy-driven ecological network in the Three-North Shelterbelt region of China - Mu, Haowei; Li, Xuecao; Ma, Haijiao; Du, Xiaoping; Huang, Jianxi; Su, Wei; Yu, Zhen; Xu, Chen; Liu, Hualiang; Yin, Dongqin; Li, Baoguo (Landscape and urban planning, 2022)
•We built a policy-driven regional ecological network in China.•We evaluated the corridors in the network using the space syntax approach.•We identified vulnerable regions from the ecological network.•We applied the ecological network for human footprint and biodiversity analyses. The Three-North Shelterbelt (TNS) program is one of China's major ecological restoration projects over the past few decades. However, evaluation of the ecological network in the TNS region has not been explored yet, in the face of intensified human activities. This study evaluated the ecological network in the TNS region from a policy-driven perspective (i.e., nature reserves). First, we mapped the ecological resistance surface in the TNS region using multiple remotely sensed ecological indicators. Then, using the derived resistance surface, we generated the ecological network and evaluated its connectivity (e.g., corridors) using the space syntax approach. Finally, we investigated the intensity of human activities and the occurrence of species around the derived ecological network. We found the ecological network is denser in humid regions than in arid areas. There are several vulnerable regions in the southern part of the Qilian Mountains and the northern part of Shaanxi. Besides, we observed overall consistent decreasing trends of human activities and species numbers along with the increase of distance to the ecological network, suggesting these corridors of ecological network play a crucial role in maintaining the biodiversity, although they are also under severe stresses of intensified human activities. Our study provides a paradigm of generating the ecological network at a large scale (i.e., the entire TNS region), showing great potential to support the phase III TNS program for sustainable development of ecological resources.